2019
DOI: 10.1016/j.apsusc.2019.04.131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface morphologies and chemistry of paper on deposited collagen

Abstract: Paper-based platforms for biological studies have received significant attention given that cellulose is ubiquitous, biocompatible, and can be readily organized into tunable fibrous structures. In the latter form, effect of complexity in surface morphologies (roughness, porosity and fiber organization) on cell-substrate interaction have not been thoroughly explored. We infer that altering the properties of a fibrous material should lead to significant changes in cellular microenvironment and direct the deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…For example, analyzing the specific variants of collagen present, as well as other ECM components, would allow for the full ECM composition of in vitro muscle and adipose cells to be compared with that of in vivo tissue, providing valuable insights into how closely the in vitro model replicates the in vivo scenario. In future work, it may also be interesting to look at the impact of surface roughness on collagen deposition, as studies have shown modulated collagen deposition with different substrate surface morphology. , For instance, Bachhuka et al found increased deposition of collagen I and III on samples featuring 38 or 68 nm nanoparticles compared to planar controls …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…For example, analyzing the specific variants of collagen present, as well as other ECM components, would allow for the full ECM composition of in vitro muscle and adipose cells to be compared with that of in vivo tissue, providing valuable insights into how closely the in vitro model replicates the in vivo scenario. In future work, it may also be interesting to look at the impact of surface roughness on collagen deposition, as studies have shown modulated collagen deposition with different substrate surface morphology. , For instance, Bachhuka et al found increased deposition of collagen I and III on samples featuring 38 or 68 nm nanoparticles compared to planar controls …”
Section: Resultssupporting
confidence: 82%
“…In future work, it may also be interesting to look at the impact of surface roughness on collagen deposition, as studies have shown modulated collagen deposition with different substrate surface morphology. 48,49 For instance, Bachhuka et al found increased deposition of collagen I and III on samples featuring 38 or 68 nm nanoparticles compared to planar controls. 48 3.5.…”
Section: Ecm Deposition By Adipocytes and Myocytes On Filmsmentioning
confidence: 99%